Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1007/bf02783312
|View full text |Cite
|
Sign up to set email alerts
|

An elemental correlation study in cancerous breast tissue by total reflection x-ray fluorescence

Abstract: The total reflection x-ray fluorescence method (TRXRF) has been employed to determine of P, S, K, Ca, Cr, Mn, Fe, Ni, Cu, Zn, Se, Rb, Sr, and Pb concentration in the benign breast tumor tissue from 68 women and in the cancerous breast tissue from 26 women. Concentrations of most of elements show enhancement in cancerous breast tissue. Examined elements compete for binding sites in the cell, change its enzymatic activity, and exert direct or indirect action on the carcinogenic process accelerating the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 14 publications
3
32
0
4
Order By: Relevance
“…Slightly higher Pb levels in the malignant breast tissues compared with the normal tissues have been reported in a US study [32]. Majewska et al [16] have reported enhanced concentrations of many trace elements in malignant breast tissues and suggested that these elements compete for the binding sites in the cell, change its enzymatic activity, and exert direct or indirect action on the carcinogenic processes, accelerating the growth of tumors, and that the inhibition of enzymes caused by the variation in trace element concentrations results in the immunological breakdown of the body system.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Slightly higher Pb levels in the malignant breast tissues compared with the normal tissues have been reported in a US study [32]. Majewska et al [16] have reported enhanced concentrations of many trace elements in malignant breast tissues and suggested that these elements compete for the binding sites in the cell, change its enzymatic activity, and exert direct or indirect action on the carcinogenic processes, accelerating the growth of tumors, and that the inhibition of enzymes caused by the variation in trace element concentrations results in the immunological breakdown of the body system.…”
Section: Resultsmentioning
confidence: 91%
“…Epidemiological studies showed that the majority of the factors leading to the development of malignant tumor in humans have arisen from environmental factors including the work environment, followed by nutritional habits as well as viral attacks and only meagerly as consequences of genetic predispositions [14,15]. Several studies have focused on the relationship between trace metal and breast cancer in humans, which indicated that the trace metals may influence the carcinogenic process [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Garg et al (1994) and Ng et al (1997) utilised Neutron Activation Analysis (NAA) to study paired breast tissue specimens (healthy and tumours), while the same technique was employed by Kanias et al (1994) to compare samples of fibrocystic disease and fibroadenoma (benign breast tumour). X-Ray Fluorescence (XRF) has been used by Rizk and Sky-Peck (1984) to study paired samples, while Total Reflection XRF was utilised by Majewska et al (1997) to compare benign to malignant breast tumours. More recently studies by our group have shown statistically significant changes in levels of copper, iron, zinc and potassium in breast tissue, these changes being associated with cancer (Geraki et al 2002, Geraki et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of trace elements in the scalp hair of breast cancer patients suggested that these elements compete for the binding sites in the cell, change its enzymatic activity, and exert direct or indirect action on the carcinogenic progress, accelerating the growth of tumors. The inhibition of enzymes caused by variation in trace element concentrations may result in immunological breakdown of the body system [35]. The quartile distribution of selected elements in the scalp hair of three donor groups is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%